Islã e terror: estratégias de construção na mídia impressa - Moreira, Deodoro José (2009)
This research investigates the manners of construction of the Other Islamic in print of national circulation weekly magazines - Carta Capital, Época, IstoÉ e Veja - , taking as corpus reports transmitted in two different periods: September 12, 2001 to December 31, 2001, months that they mark the period understood among the day after to the air raids against the United States and the subsequent invasion of Afghanistan, that it happened in October of 2001, and March 1, 2003 to June 30, 2003, months that they include previous and subsequent periods to the invasion of Iraq, that felt in March of 2003. The diversity of discursive strategies is investigated and/or communicative used by the print media journalistic to build this event, redefines facts. Being considered that such strategies look for to "capture" the reader and to do with that he identifies, starting from the enunciation contract, with certain interpretations of the facts, becomes essential a discursive analysis of the text (verbal and non-verbal) to understand that roads are trodden to exercise that "attraction". Besides the theories of critical discourse analysis, we supported in the works philosophical/sociological of Laclau, Baudrillard and i ek, to build the conductive threads of this work. For analysis of the texts, we adopted the critical analysis of discourse, starting from Norman Fairclough. Already the theories of more philosophical stamp (in some cases to multidiscipline, as of Laclau, Baudrillard and i ek), they went fundamental to examine the context of the political point of view, to know, of the discursive formations in search of the hegemony and of totalization over the action, involving positioning and ideologies in global reality. In that way, it was possible to guide the research second a critical positioning in relation to the print media. The analysis was divided in six thematic axes. They are them: globalization, terrorism, widespread war, exception state, fundamentalism and hegemony